Two sides of intensive parenting: Present and future dimensions in contemporary relations between parents and children in Spain. (February 2013) - Gómez Espino, Juan Miguel
The objective of this article is to identify and analyse discourses in Spain on intensive parenting in the context of the changes that have taken place in relations between parents and their children in contemporary societies. To do this, the author analyses the discourses from 16 in-depth interviews carried out with parents and from 14 focus groups of 11- and 12-year-old children. The article makes a distinction between two analytical dimensions of intensive parenting: intensive parenting for the future, which refers to the growing emphasis of parents on children's cognitive development and education, and intensive parenting for the present, which refers to supervision and protection of children in the face of unexpected events affecting their safety and well-being. The article addresses how the perception of new risks and uncertainties strongly encourages different forms of control and greater individualism as families attempt to maximize the advantages of their own members, generating increasingly inegalitarian effects.